Gender gap variation across assessment types: Explanations and implications. (December 2022) - Graetz, Georg; Karimi, Arizo
Abstract: Using Swedish population data, we document that girls outperform boys by a third of a standard deviation in school grades, whereas a gap of similar magnitude but opposite sign persists in SAT scores in the sample of non-randomly selected test takers. We establish that grades capture different attributes than SAT scores, which accounts for much of the variation in gender gaps. A model of SAT participation illustrates how women's greater participation—driven by traits not rewarded by higher scores—leads to their negative selection on observed and unobserved traits. We explore the quantitative importance of this mechanism and conclude that while selection is important, it fails to account for a substantial fraction of the gender gap in SAT scores, suggesting the possibility that the SAT penalizes women.